1998
DOI: 10.1007/s101200050005
|View full text |Cite
|
Sign up to set email alerts
|

Severe atrophic gastritis with Helicobacter pylori infection and gastric cancer

Abstract: Abstract:Background. We conducted a case-control study to evaluate whether patients with severe gastric atrophy (indicated by serum pepsinogen concentration) have a high risk of gastric cancer. Methods. At the time of diagnosis of gastric cancer, sera from 301 patients (cases) and 602 sex-and age-matched cancer-free individuals (controls) were tested for the presence of antiHelicobacter pylori IgG antibody (HM-CAP enzyme-linked immunoassay [ELISA] kit; Kyowa Medix, Tokyo, Japan) and serum pepsinogen (PG) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
1
12
1
1
Order By: Relevance
“…In patients with extensive mucosal atrophy, the spontaneous disappearance of H. pylori was also observed, indicating that the mucosa of IM or CAG patients without H. pylori infection had undergone precancerous mucosal changes. 10,16 In this study, the frequency of the C allele in the IM or CAG without H. pylori infection group was significantly higher than that in the H. pylori-negative noncancer controls. This result indicated that this Ϫ511 T-to-C base transition may be important for the mucosal atrophy of the stomach.…”
Section: Discussioncontrasting
confidence: 71%
“…In patients with extensive mucosal atrophy, the spontaneous disappearance of H. pylori was also observed, indicating that the mucosa of IM or CAG patients without H. pylori infection had undergone precancerous mucosal changes. 10,16 In this study, the frequency of the C allele in the IM or CAG without H. pylori infection group was significantly higher than that in the H. pylori-negative noncancer controls. This result indicated that this Ϫ511 T-to-C base transition may be important for the mucosal atrophy of the stomach.…”
Section: Discussioncontrasting
confidence: 71%
“…Compared with ''normal'' pepsinogen and negative H. pylori antibody group, the hazard ratios (95% CI) of developing gastric cancer for normal pepsinogen and positive H. pylori antibody group, atrophic pepsinogen and positive H. pylori antibody group, and atrophic pepsinogen and negative H. pylori antibody group were 1.1 (0.4-3.4), 6.0 (2.4-14.5), and 8.2 (3.2-21.5), respectively. In addition, a casecontrol study conducted in Japan showed the largest OR of gastric cancer in the positive pepsinogen and negative H. pylori infection group compared with other combination groups (53). In our study, although a statistically significant, f5-fold risk of developing gastric cancer was observed among those who were H. pylori IgG-seronegative and pepsinogen-positive, the PAF (95% CI) was calculated as only 2.6% (1.0-4.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that multiple gastric carcinomas were correlated signifi cantly to the distribution of atrophic mucosa in the stomach and the degree of intestinal metaplasia in the surrounding mucosa, and multivariate analysis confi rmed the latter as a signifi cant independent factor. Recent studies have shown that H. pylori not only causes peptic ulcer and gastritis but also exhibits a strong correlation to gastric carcinomas [27][28][29]. The WHO/International Agency for Research on Cancer (IARC) recognized H. pylori as a defi nite carcinogen in 1994 [30].…”
Section: Discussionmentioning
confidence: 99%